A Functional Genomics View of Gibberellin Metabolism in the Cnidarian Symbiont Breviolum minutum - Wu, Dan; Yang, Lin; Gu, Jiahua; Tarkowska, Danuse; Deng, Xiangzi; Gan, Qinhua; Zhou, Wenxu; Strnad, Miroslav; Lu, Yandu (Frontiers in Plant Science, 2022)
Dinoflagellate inhabitants of the reef-building corals exchange nutrients and signals with host cells, which often benefit the growth of both partners. Phytohormones serve as central hubs for signal integration between symbiotic microbes and their hosts, allowing appropriate modulation of plant growth and defense in response to various stresses. However, the presence and function of phytohormones in photosynthetic dinoflagellates and their function in the holobionts remain elusive. We hypothesized that endosymbiotic dinoflagellates may produce and employ phytohormones for stress responses. Using the endosymbiont of reef corals Breviolum minutum as model, this study aims to exam whether the alga employ analogous signaling systems by an integrated multiomics approach. We show that key gibberellin (GA) biosynthetic genes are widely present in the genomes of the selected dinoflagellate algae. The non-13-hydroxylation pathway is the predominant route for GA biosynthesis and the multifunctional GA dioxygenase in B. minutum has distinct substrate preference from high plants. GA biosynthesis is modulated by the investigated bleaching-stimulating stresses at both transcriptional and metabolic levels and the exogenously applied GAs improve the thermal tolerance of the dinoflagellate. Our results demonstrate the innate ability of a selected Symbiodiniaceae to produce the important phytohormone and the active involvement of GAs in the coordination and the integration of the stress response.